Pemberdayaan Kelompok Petani Kopi Karang Rejo untuk Meningkatkan Pemanfaatan Daun Kopi Menjadi Layak Konsumsi - Ardian Asyhari; Feti Yunita Sari; Nopal Reza Efendi; Dinda Nurjanah; Ocha Septianti; Bayu Putra; Dicy Maulana; Dayangku Intan; Andrea Bagas; Nurul Apriyadi; Muhammad Benard; Fauza Farida; Amar Syafaat; Indah Veronika (Jurnal Pengabdian Pada Masyarakat, 2020)
EMPOWERMENT OF KARANG REJO FARMER GROUP TO IMPROVE THE UTILIZATION OF COFFEE LEAVES INTO CONSUMPTION. Coffee ore is the main asset of Pekon Karang Rejo, Ulubelu Subdistrict, Tanggamus Regency, however, coffee ore is not the only commodity that can be processed as a source of income, even coffee leaves can be processed into an innovative product and rich in health benefits. The optimal use of natural resources can increase productivity in this village, not only in terms of material use value but also potentially, besides that the community can expand their horizons with the existence of this activity. The coffee leaves in Pekon are not utilized optimally because of the lack of community knowledge, and the accessibility to technology that is quite difficult so that people do not innovate. Therefore, the purpose of this activity is to provide education about the management and efficacy of coffee leaf tea as an abundant available natural material in this Pekon and its modern marketing. The method used is to provide counseling or outreach and with the ABCD (Asset Based Community Development) approach. Based on this it is expected that the community can innovate in utilizing available natural materials.